Chronic pramipexole treatment increases tolerance for sucrose in normal and ventral tegmental lesioned rats - Dardou, David; Chassain, Carine; Durif, Franck (Frontiers in Neuroscience, 2015)
The loss of dopamine neurons observed in Parkinson’s disease (PD) elicits severe motor control deficits which are reduced by the use of dopamine agonists. However, recent works have indicated that D3-preferential agonists such as pramipexole can induce impulse control disorders such as food craving or compulsive eating. In the present study, we performed an intermittent daily feeding experiment to assess the effect of chronic treatment by pramipexole and VTA bilateral lesion on tolerance for sucrose solution. The impact of such chronic treatment on spontaneous locomotion and spatial memory was also examined. Changes in sucrose tolerance could indicate the potential development of a change in food compulsion or addiction related to the action of pramipexole. Neither the bilateral lesion of the VTA nor chronic treatment with pramipexole altered the spontaneous locomotion or spatial memory in rats. Rats without pramipexole treatment quickly developed a stable intake of sucrose solution in the 12h access phase. On the contrary, when under daily pramipexole treatment, rats developed a stronger and ongoing escalation of their sucrose solution intakes. In addition, we noted that the change in sucrose consumption was sustained by an increase of the expression of the dopamine 3 receptor in the core and the shell regions of the nucleus accumbens. The present results may suggest that long term stimulation of the dopamine 3 receptor in animals induces a strong increase in sucrose consumption, indicating an effect of this receptor on certain pathological aspects of food eating.